Constrained shape optimization of free-form shells considering material creep. Issue 10 (3rd October 2022) - San, Bingbing; He, Haiyun; Feng, Dongming; Qiu, Ye; Huang, Yanting
Abstract : Shape optimization is an effective tool for designing free-form structures for a variety of design objectives. Aiming at long-term structural performance, a computational framework is presented for performing shape optimization of free-form shells while considering material creep. The material creep model is incorporated into a gradient-based optimization algorithm using a viscoelastic finite element model. Non-uniform rational B-spline (NURBS) is employed to parameterize the free-form geometric shapes of shells. Optimization is conducted for minimizing the shell volume subject to constraints of specified maximum displacement. The results demonstrate that it is necessary to consider creep when designing shells made of viscoelastic materials for long-term performance.